Vandetanib for the Management of Advanced Medullary Thyroid Cancer: A Real-World Multicenter Experience - Kim, Mijin (Endocrinol Metab (Seoul), 2020)
BACKGROUND: Vandetanib is the most widely used tyrosine kinase inhibitor for the treatment of patients with advanced medullary thyroid cancer (MTC). However, only limited data regarding its use outside clinical trials are available. We aimed to evaluate the efficacy and safety of vandetanib in patients with advanced MTC in routine clinical practice. METHODS: In this multicenter retrospective study, 12 patients with locally advanced or metastatic MTC treated with vandetanib at four tertiary hospitals were included. The primary outcome was the objective response rate (ORR) based on the Response Evaluation Criteria in Solid Tumors. The progression-free survival (PFS), overall survival (OS), and toxicities were also evaluated. RESULTS: Eleven patients (92%) had distant metastasis and 10 (83%) had disease progression at enrollment. Partial response was observed in five patients (ORR, 42%) and stable disease lasting ≥24 weeks was reported in an additional five patients (83%). During the median 31.7 months of follow-up, disease progression was seen in five patients (42%); of these, two died due to disease progression. The median PFS was 25.9 months, while the median OS was not reached. All patients experienced adverse events (AEs) which were generally consistent with the known safety profile of vandetanib. Vandetanib was discontinued in two patients due to skin toxicity. CONCLUSION: Consistent with the phase III trial, this study confirmed the efficacy of vandetanib for advanced MTC in terms of both ORR and PFS in the real-world setting. Vandetanib was well tolerated in the majority of patients, and there were no fatal AEs.